A Comparative Analysis of Neural Machine Translation (NMT) and Human Translation: A Case Study of The Fable "The Frog and The Crocodile" - Samosir, Fitri (Critical Review of English-Arabic World Journal, 2025)
In the contemporary technological landscape, modern innovations have woven themselves into the fabric of everyday human existence. Among these advancements is Neural Machine Translation (NMT), a tool that has seen significant progress alongside broader technological strides. Yet, when it comes to translating certain types of content like fables, machine translator outputs frequently exhibit innaccuracies in handling cultural nuances. The results from machine translation and human translation in rendering fables are bound to diverge in notable ways. This study aims to compare the differences translation results of the fable story "The Frog and The Crocodile" between human translation and neural machine translation (NMT) in terms of accuracy, fluency, and cultural adaptation. The method used in this study was qualitative content analysis. The fable story entitled "The Frog and The Crocodile" served as a source of data. The results shows that human translation and machine translation provide several differences in translating fable. The machine translation which used literal translation often losing the nuance and meaning of the story while human translation can provide a better translation results in terms accuracy, fluency, and cultural nuances.